ETUDE DU COMPORTEMENT AU REPOS ET DES PREFERENCES TROPHIQUES DE ANOPHELES GAMBIAE DANS LA VILLE D’ADZOPE, COTE D’IVOIRE - Adja, Akré Maurice; Assare, Kouassi Rufin; Assi, Serge Brice; N’Dri, Louis; Yapi, Ahoua; Ngoran, Kouakou Eliézer (European Scientific Journal, ESJ, 2015)
An entomological follow up, carried out by house resting collection and outdoor resting collections was achieved from June 2006 to September 2008 in Adzope, a town located in South-west Côte d’Ivoire, in the forest zone. This study aimed at identifying the origin of the An. gambiae females bloodmeals. In total, 539 mosquitoes were collected, 390 house resting mosquitoes and 149 outdoor resting ones. The mosquitoes collected in the two environments belong to 3 genera: Anopheles (92.5 %), Culex (7.2 %) and Mansonia(0.2 %). An. gambiae was the only anopheles species collected. The study of its resting behavior reveals the existence in Adzope of two populations: endophilic and exophilic. The origin of 60 bloodmeals of this species was identified by the PCR-heteroduplex. In houses, the bloodmeals were collected on humans (97%) and goats (3%). In outdoor shelters, the collection was made on humans (87.5%), birds (3%) and cows (1.5%). The bloodmeals from unknown origins were 1.5%. Actually, the poultry was the host preference for animal-feeding females. An. gambiae presents a high anthropophilic rate and therefore a threat for Adzope population.